Defining the noma research agenda. - Anaïs Galli; Marianne Comparet; Daniel Argaw Dagne; Denise Baratti-Mayer; Thi H Cao; Philippe J Guérin; Maria Guevara; Manuel W Hetzel; Claire Jeantet; Emmanuel Kabengele Mpinga; Valter Muendane; Mulikat Okanlawon; et al. (PLoS Neglected Tropical Diseases)
• A 1-day symposium brought together over 100 individuals with lived experience of noma, expertise in neglected tropical diseases, and public health, including researchers, health advocates, and clinicians. The involvement of noma survivors was invaluable and added an important perspective in defining the research agenda. • The most pressing research needs identified were: ○ Clear case definition of noma ○ Early case detection and robust surveillance ○ Psychosocial and economic impact of noma ○ Decision support for diagnosing acute necrotizing gingivitis and associated antibiotic regimen(s) with treatment duration ○ Deeper understanding of risk factors and social determinants ○ Identification of effective information, education, and communication strategies ○ Effectiveness of surgical services ○ Testing decentralized follow-up for patients • An important conclusion was that noma research and control activities must be integrated across sectors and disciplines, such as neglected tropical diseases, oral health, nutrition, and child health programs including immunization.